Adherence to treatment among hypertensives of rural Kerala, India - Arjun Balasubramanian; Sreejith S Nair; P S Rakesh; K Leelamoni (Journal of Family Medicine and Primary Care, 2018)
Introduction: Poor adherence is an important barrier to adequate blood pressure control among the diagnosed hypertensives. The study aimed at assessing the level of adherence to medication and to identify factors associated with it in people with hypertension in a rural population of Kerala. Subjects and Methods: A community-based cross-sectional study was conducted in July 2016 among 189 known hypertensives of a rural population in Kerala. Data was collected by interview method using a semistructured questionnaire. Medication adherence was assessed using 4-item Morisky Medication Adherence Scale. Chi-square was used to test the significance of association, and logistic regression was done to identify independent predictors along with odds ratio (OR). Result: The mean age of study participants was 65.12 ± 11.71 years and the mean duration of disease was 8.69 ± 7.99 years. High adherence was seen in 46% of the patients, while medium and low adherence was seen in 41.3% and 12.7%, respectively. Risk factors of poor adherence identified were poor knowledge of the complications (OR – 2.120; 95% confidence interval [CI] 1.110–4.048), availing government pharmacy (OR – 2.379; 95% CI 1.131–5.004), and being asymptomatic at the time of diagnosis (OR – 2.120; 95% CI 1.110–4.048). Conclusion: Adherence to medication among people with hypertension in the current study is poor. A comprehensive strategy to improve adherence to antihypertensive medications is the need of the hour.